Exceptional mechanical properties of aluminum matrix composites with heterogeneous structure induced by in-situ graphene nanosheet-Cu hybrids. (1st April 2022) - Pu, Bowen; Zhang, Xiang; Chen, Xiaofeng; Lin, Xiaobin; Zhao, Dongdong; Shi, Chunsheng; Liu, Enzuo; Sha, Junwei; He, Chunnian; Zhao, Naiqin
Abstract: Designing heterogeneous structures is a promising pathway for overcoming the trade-off between strength and toughness in metal matrix composites (MMCs). Herein, we report an innovative strategy for fabricating graphene nanosheet-Cu reinforced Al matrix (GNS-Cu/Al) composites with heterogeneous structure. This strategy involves the consolidation of unique composite powders with core-shell grain structure, which are synthesized with the aid of in-situ GNS-Cu hybrids. Results reveal that the fabricated GNS-Cu/Al composite exhibits multiple microstructural heterogeneities, including both heterogeneous grain structure and reinforcement spatial distribution, which endow the composite with a prominent combination of tensile strength of ∼437 MPa, fracture elongation of ∼12.5% and toughness of ∼48.7 MJ m −3 . It is confirmed that such microstructural heterogeneities in GNS-Cu/Al composite contribute significant hetero-deformation induced (HDI) stress strengthening and sustained strain hardening, making the key mechanical properties of GNS-Cu/Al considerably outperform the counterpart of Cu/Al composite. Moreover, the coordinated deformation and crack bridging/blunting behaviors are demonstrated to be responsible for the exceptional toughness of GNS-Cu/Al composite. This work offers a promising bottom-up tactic to fabricate Al matrix composites with heterogeneous structures and superior mechanical performances for structural applications. Graphical abstract: Image 1